Security of tenure in the urban context - Brighton, N; Farmer, K; Nordlie, Ø (Refugee Studies Centre, University of Oxford, 2017)
Addressing the lack of secure tenure and the risk of forced eviction is one of the defining characteristics of urban shelter response.